2021
DOI: 10.1186/s43055-021-00595-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of functional imaging; DWI, ADC and 18F-FDG PET/CT in the evaluation of HCC treatment response after transarterial chemoembolization

Abstract: Background The transcatheter arterial chemoembolization (TACE) is one of the treatment lines for patients with hepatocellular carcinoma (HCC), this study was conducted to assess the role of functional imaging including the DWI, ADC and 18F-2-fluoro-2-deoxyglucose (FDG) positron emission tomography-computed tomography (PET/CT) for detection of residual HCC after TACE as compared to the structural liver imaging reporting and data system (LI-RADS). Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…While CT was originally the most common imaging modality for monitoring HCC patients after TACE. However, its accuracy can be limited by the following pitfalls: beam-hardening artifacts from highattenuation lipiodol masking intra-lesional viable tumor and the significantly thinner feeding arteries of the residual tumor reducing contrast enhancement of the tumor (7) . FDG PET/CT and MRI are better than CT for detecting hepatic focal lesions (7) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While CT was originally the most common imaging modality for monitoring HCC patients after TACE. However, its accuracy can be limited by the following pitfalls: beam-hardening artifacts from highattenuation lipiodol masking intra-lesional viable tumor and the significantly thinner feeding arteries of the residual tumor reducing contrast enhancement of the tumor (7) . FDG PET/CT and MRI are better than CT for detecting hepatic focal lesions (7) .…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, the study performed by Nashi et al, (14) showed that PET/CT had a sensitivity of 74.60%, specificity of 57.54%, PPV of 87.5%, NPV of 90.0% as well as accuracy of 88.2% respectively in the assessment of HCC patients after therapeutic interventions. On the other hand, Abdelrahman et al, (7) established that the sensitivity, specificity, and accuracy of FDG PET/CT for the detection of residual viable tumoral tissue after TACE were 81.5%, 75%, and 80% respectively, whereas Kim et al, (13) reported sensitivity of 87.5%, specificity of 71.4% and accuracy of 80% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study ofAbdelrahman et al 12 The qualitative DWI had aisensitivityiandispecificityof 77.8% and 75% for detecting remnant viable HCC after TACE,irespectively. The quantitative ADC value had a higher sensitivity than the DWI for detecting remnant HCC, with aisensitivityiandispecificityof 81.5% and 75%,irespectively, at an ADC cut off value of 1.32 103 mm 2 /s.…”
Section: Hcc Patients (N=30)mentioning
confidence: 97%